Social Service Model and Value Evaluation of Libraries under Sharing Economy - Ping Liu; Lijing Cai; Liqin Luo (Discrete Dynamics in Nature and Society)
Libraries are increasingly marginalized by the information construction of electronic resources retrieval platform. This calls for a novel social service model (SSM) for libraries to enhance the overall value of their various service functions. Therefore, this paper explores the SSM and value evaluation of libraries under sharing economy. Firstly, the SSM of libraries was broken down into a base layer, a physical layer, and a virtual layer, and an evaluation index system (EIS) was constructed for the social sharing service (SSS) value of libraries. Next, the SSS value of libraries was evaluated and predicted, and the functional value of the SSM of libraries was analyzed in detail. The proposed prediction model was proved effective through experiments, and the SSS functions of libraries were valued.